STEM-Based LKPD Development and Contextual Problems to Improve Explanation, Concluding, and Evaluating Skills - Kiswari, Lusinta; Singgih, Suwito; Muhlisin, Ahmad (Phenomenon : Jurnal Pendidikan MIPA, 2022)
One comprehensive and integrated learning approach is the STEM approach. This approach can improve students' critical thinking skills if supported by teaching materials, one of which is LKPD. This study aims to produce a valid, practical, and effective STEM-based LKPD product to improve students' critical thinking skills. The method used in this study is the research and development method. A validity test has been carried out consisting of a product validity test that is declared valid and suitable for use with a percentage of 80.9%. Practicality tests conducted by teachers obtained an average result of 83% and students of 87%. The effectiveness test is carried out with an n-gain test and an effect size test. Each of them obtained a result of 0.68 in the medium category and 2.7 in the high category. So, it can be concluded that STEM-based LKPD is effective in improving students' critical thinking skills.